Effect of Fathers' Involvement in the Care of Neonates with Congenital Anomalies on Paternal Bonding: A Quasi-Experimental Study - Somayeh Rahimi; Manijeh Nourian; Maryam Varzeshnejad; Maryam Mahdizadeh; Malihe Nasiri (Mashhad University of Medical Sciences, 2022)
Background: The birth of a neonate with a congenital anomaly who is admitted to the neonatal intensive care unit (NICU) is a threat to the formation of paternal bonding.  The present study aimed to assess the effect of fathers' involvement in the care of neonates with congenital anomalies on father-neonate bonding in NICUs. Methods: This quasi-experimental study with a control group was conducted on fathers of neonates with congenital anomalies admitted to the NICU of Mofid Hospital affiliated to Shahid Beheshti University of Medical Sciences in Tehran, Iran, from January 2019-September 2021. A total of 60 participants were selected via the convenience sampling method and randomly assigned to two groups of experimental and control. The Mother-to-Infant Bonding Scale was used to collect the needed data. The intervention lasted for four weeks. In the first week, fathers attended three sessions on how to provide care; thereafter, over the next three weeks, fathers became involved in the care of their newborns. The data were analyzed in SPSS software (version 21), and a p-value less than  0.05 was considered statistically significant. Results: After the intervention, there was a statistically significant difference between the mean scores of paternal bonding in two groups of control (4.41±2.51) and experimental (2.21±2.37) (P=0.001), with a lower score indicating a stronger paternal bond. The mean paternal bonding scores decreased to 6.59±17.1 and 4.89±0.54 in the two groups of intervention and control, respectively. The obtained results pointed to a significant difference between the two groups in terms of alterations in bonding scores (P<0.001). Conclusion: As evidenced by the results of the present study, the participation of fathers in the care of their neonates with congenital anomalies was associated with a greater improvement of father-neonate bonding. Therefore, nurses need to devote more assiduous attention to the involvement of fathers in the care of these neonates.